1997
DOI: 10.1093/oxfordjournals.aje.a009235
|View full text |Cite
|
Sign up to set email alerts
|

Cholera in Lima, Peru, Correlates with Prior Isolation of Vibrio cholerae from the Environment

Abstract: The authors utilized a recently developed DNA probe technique to obtain quantitative data on occurrence of Vibrio cholerae in samples collected monthly from 12 environmental sites in Lima, Peru, from November 1993 through March 1995. Peak V. cholerae counts ranged from 10(2)/ml to 10(5)/ml, with the highest counts in sewage-contaminated areas and irrigation water. With our methodology, no V. cholerae cases were detected at any site during the winter months of July through October. Counts were detectable in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 16 publications
2
35
0
1
Order By: Relevance
“…The same probe but with a nonradioactive label was used in a study conducted in Lima, Peru, where all ctx probe-positive colonies were V. cholerae, confirmed by standard microbiological methods (13). Based on these results, and the exclusion from analysis of any filters lacking clear positive and negative control results, the probe data provide a reasonable estimate of total ctx-positive V. cholerae present in the samples examined.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The same probe but with a nonradioactive label was used in a study conducted in Lima, Peru, where all ctx probe-positive colonies were V. cholerae, confirmed by standard microbiological methods (13). Based on these results, and the exclusion from analysis of any filters lacking clear positive and negative control results, the probe data provide a reasonable estimate of total ctx-positive V. cholerae present in the samples examined.…”
Section: Resultsmentioning
confidence: 86%
“…Cholera toxin oligonucleotide labeling. For these studies we utilized a DNA oligonucleotide probe that has been shown to have essentially 100% sensitivity and specificity for the cholera toxin gene (ctx) in prior laboratory and field studies (13). Of particular note, the probe is drawn from a portion of ctx that is divergent from the Escherichia coli heat-labile toxin (LT) gene, permitting differentiation between strains carrying cholera toxin and heat-labile toxin genes (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, it has been demonstrated that V. cholerae can be transmitted to humans via the environment, in drinking and cooking water, irrigation water, and shellfish. With active environmental monitoring systems using epifluorescence microscopy and molecular methods for direct detection, the presence of V. cholerae, ctxAB-carrying bacteria, and vibriophages in sewage and surface waters has been shown to precede the onset of cholera outbreaks by 1 to 4 months (52,104,106,154). Furthermore, cholera is dose dependent, with at least 10 4 cells required for infection (69).…”
Section: Seasonalitymentioning
confidence: 99%
“…There has been much speculation as to the cause of this reemergence and whether there has always been an environmental reservoir for Vibrio cholerae in Latin America. Since 1991, seasonal patterns of cholera outbreaks have been well documented in Central and South America, with the largest numbers of cases occurring during the warm, summer months (January to March) (7,21).…”
mentioning
confidence: 99%